Faktor-Faktor yang Mempengaruhi Minat Pemanfaatan Computer-Assisted Audit Techniques (CAATs) oleh Auditor: Pendekatan UTAUT - Septari, Al-Iqrom; Hizazi, Ahmad; Wahyudi, Ilham; Yuliusman, Yuliusman (Magister Ilmu Akuntansi Universitas Jambi, 2025)
The adoption of CAATs in Indonesia (especially in the southern part of Sumatra) is still relatively low, despite the efforts of auditing professional bodies to encourage the application of modern audit technologies among audit firms to deal with the rapid growth in information technology usage among business organizations. This study uses the Unified Theory of Acceptance and Use of Technology (UTAUT) to explore of CAATs' usage and try to find answers to what factors may affect their adoption and acceptance. Using 86 valid responses from external auditors, the paper found that CAATs adoption is influenced by performance expectancy, effort expectancy, facilitating conditions, and self-efficacy. The findings suggest that policymakers should encourage external auditors to use CAATs by educating them about the advantages of doing so, improving their skills through increased CAATs training programs, creating incentive systems that encourage auditors to use CAATs, increasing investments in the management and technical infrastructure that supports CAATs, and using both intrinsic and extrinsic motivation.